Growth and biochemical responses of red chili (Capsicum annuum L) under drought conditions with 6-Benzylaminopurine application - Sihotang, Tambun; Siregar, Luthfi Aziz Mahmud; Rahmawati, Nini (Institute of Computer Science (IOCS), 2024)
The purpose of this research is to assess how red chili plants (Capsicum annuum L.) develop and react biochemically to drought stress, as well as how cytokinin treatment affects these plants. The study employed a factorial Randomized Block Design (RAK) with three replications and two components, namely the degree of drought with three stages, comprising: K1 has an 80% soil water content, K2 has a 60% soil water content, K3 has a 40% soil water content, and S0, S1, S2, and S3 have 0 ppm, 10 ppm, 20 ppm, and 30 ppm of 6-benzylaminopurine concentration, respectively. Plant height, leaf count, root length, flowering age, total and aqueous chlorophyll content, activity of antioxidant enzymes (e.g., superoxide dismutase and peroxide dismutase), and hydrogen peroxide as a signal for plant molecules against dehydration stress are among the parameters assessed. The findings demonstrated that red chili plants under drought stress experienced slower growth, as seen by a reduction in height and leaf count as well as earlier flowering. However, by raising plant height, leaf count, and chlorophyll levels (a, b, and total), cytokinin treatment was able to lessen the deleterious impacts of drought. When treated with 10 ppm 6-Benzylaminopurine, the enzyme activity of superoxide dismutase, peroxide dismutase, and hydrogen peroxide increased, but at other dosages, it tended to decrease, suggesting a slight but noticeable increase in plant defense mechanisms against oxidative stress. Therefore, giving red chili plants 10 parts per million of cytokinin may be a useful tactic for enhancing their resistance to drought stress.